Tourism communication strategies in increasing visitor interest in the Punti Kayu Nature Tourism destination, Palembang City - Feronika Feronika; Nurul Aryanti; Ahmad Iman Mulyadi (Priviet Social Sciences Journal, 2026)
This study aimed to analyze the tourism communication strategies implemented by the management of the Punti Kayu Nature Tourism Park in Palembang City to enhance tourist interest in visiting. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation. Data were collected from four informants consisting of one destination manager, one institutional representative, and two repeat visitors. The findings indicate that management applies communication strategies centered on the use of digital media, such as Instagram, TikTok, and Facebook, as primary promotional channels. These strategies are considered effective, efficient, and capable of reaching the young tourist segment. In addition, interpersonal communication through events and community collaboration further strengthens tourist engagement. The main challenges include limited promotional budgets, insufficient digital marketing training, and fluctuations in visitor numbers due to post-pandemic economic conditions. The study concludes that adaptive and collaborative digital communication strategies play a crucial role in reinforcing the destination image and increasing visitor interest.